The Demographic and Behavior Determinant of Credit Card Default in Indonesia - Wahid Achsan; Noer Azam Achsani; Bayu Bandono (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2022)
The purpose of this paper is to analyze the demographic and behavioral factors that significantly affect the credit card Non-Performing Loan (NPL). This study is carried out to provide managerial recommendations for controlling credit card NPL. This study uses secondary data from Indonesia’s most significant private bank with 100,000 samples of cardholder data. Demographic factors and cardholder behavior that significantly influence credit card NPL can be used to improve the credit scoring system for new cardholders and as indicators for a behavior scoring system for existing cardholders. This research uses a probability stratified random sampling technique. Logistic regression uses demographic factors and cardholder behavior significantly affected credit card NPL. According to the logistic regression model, cardholder behavior was more likely to NPL than demographic characteristics. The number of credit cards showed the highest credit card NPL probability.How to Cite:Achsan, Wahid, Achsani, N. A, & Bandono, Bayu. (2022). The Demographic and Behavior Determinant of Credit Card Default in Indonesia. Signifikan: Jurnal Ilmu Ekonomi, 11(1), 43-56. https://doi.org/10.15408/sjie.v11i1.20215.